Staphylococcal scalded skin syndrome in a newborn. - Fernández-Fructuoso, J.R.; Sevilla-Denia, S.; Lloreda García , J.M. (European Journal of Pediatric Dermatology, 2022)
Staphylococcal scalded skin syndrome (SSSS) is a rare syndrome caused by exfoliative toxins A and B produced by Staphylococcus aureus in a primary cutaneous or extracutaneous infectious focus. SSSS is particularly common in newborns where, due to the lack of protective antibodies, toxins penetrate the bloodstream and reach the epidermis; it is possible that the immaturity of renal function plays a role in the pathogenesis of the disease by limiting the excretion of toxins. Here is reported the case of a 25-day-old newborn with SSSS.